PENGARUH KEMACETAN AKIBAT PARKIR PADA BADAN JALAN TERHADAP BIAYA OPERASIONAL KENDARAAN (STUDI KASUS JALAN GAJAH MADA PASAR FLAMBOYAN PONTIANAK) - Nody, Rian; AS, Syafaruddin; Azwansyah, Heri (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
Traffic congestion on urban roads in big cities has become a major topic that has always been a problem, especially in developing countries like Indonesia. In general, there are three factors causing congestion problems that are getting worse, namely the increasing of vehicle ownership (demand), limited resources for road construction and other transportation facilities (supply), and not yet optimal operation of existing transportation facilities (operating system). The phenomenon of congestion becomes an interesting thing to be studied, just like the congestion caused by the influence of Flamboyan Market activity to the traffic on Jalan Gajah Mada street where the number of vehicles do the parking on the road body (On street parking) causing traffic congestion. The methodology used in this research is to perform the primary data processing of field survey results and collect some information needed as secondary data.From the result of road performance analysis that happened on Gajah Mada Street on Sunday, 21 May 2017 with amount Rp 32019.231. On Monday, 22 May 2017 with the amount of Rp 32972.26. On Saturday, 27 May 2017 with the amount of Rp 32392.95, The total of all is Rp 97384.44.Keywords: On Street Parking Parking, Speed Reduction of Vehicle, Vehicle Operational Cost